External debt and economic growth of Mexico, 1971-1991 - Jhabvala, Firdaus (Estudios Económicos de El Colegio de México, 1991)
This paper provides a model of foreign debt and economic growth for Mexico, which is used to establish regions of financial and socio-political viability. The possibilities for Mexican high growth rates, given the burden of its foreign debt, are then analyzed.